The Analysis of Working Possibilities of a Power Shovel - Gierulski, W.; Płonecki, L.; Cendrowicz, J. (Engineering Transactions, 1995)
The calculation of the forces acting on the bucket during the excavation process is described in the paper. The knowledge of these forces is needed for the automation of the shovel. These forces are calculated by a computer controlling the due work of the equipment and the hydraulic feeder system. The procedure of calculation of the maximum forces acting on the excavated ground is described as well.